Sistem Pendukung Keputusan Penentuan QCC Terbaik Dengan Metode AHP Pada PT. Century Batteries Indonesia - Nurhadi Surojudin (Teknik Informatika, Universitas Pelita Bangsa, 2020)
Selection of the Best QCC Group is giving recognition to the best QCC group who actually and extraordinary do Quality Control System activities by making changes that can increase the effectiveness and efficiency of work or production. The selection of the Best QCC Group of PT Century Batteries Indonesia is held annually. In the Best Group assessment process, PT. CBI appointed an assessment team to conduct an assessment of the QCC group. However, the assessment process is still done manually so it takes a long time to process the data. In addition, the assessment is still subjective and not yet relevant to the actual situation. Based on this, in this study a decision support system was built to be used to select the best QCC group selection process at PT Century Batteries. Decision support system built based on web using the programming language PHP and MySQL as the database. The decision making method used is Analytical Hierarchy Process (AHP). This method is used to determine the weight value of each criterion, which is then carried out by a ranking process to determine the best alternative from a number of alternatives. The test carried out in this study is functional testing with the black box testing method. The test results show that the system can run properly according to its function.. Keywords: Analytical Hierarchy Process (AHP), Decision Support System